DESAIN MEDIA “E-STORYBOOK SAYU WIWIT” BERBASIS KEARIFAN LOKAL CERITA RAKYAT BANYUWANGI KELAS VII SMPN 2 BANGOREJO (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to design learning media based on local wisdom used to increase reading interest of seventh grade students at SMPN 2 Bangorejo, Banyuwangi. As well as knowing the quality of learning media based on the assessment of three experts, namely material experts, media experts and learning experts. The development of this media uses the ADDIE method, namely analysis, design, development, implementation and evaluation (product assessment). This research is at the level of development level one in the research process, namely researchers conduct research to produce product design designs that are tested internally. The design of the learning media